Directed osteogenic differentiation of human mesenchymal stem/precursor cells on silicate substituted calcium phosphate1. Issue 1 (26th June 2012) - Cameron, Kate; Travers, Paul; Chander, Chaman; Buckland, Tom; Campion, Charlie; Noble, Brendon
Abstract: Insufficient, underactive, or inappropriate osteoblast function results in serious clinical conditions such as osteoporosis, osteogenesis imperfecta and fracture nonunion and therefore the control of osteogenesis is a medical priority. In vitro mesenchymal stem cells (MSCs) can be directed to form osteoblasts through the addition of soluble factors such as β‐glycerophosphate, ascorbic acid, and dexamethasone; however this is unlikely to be practical in the clinical setting. An alternative approach would be to use a scaffold or matrix engineered to provide cues for differentiation without the need for soluble factors. Here we describe studies using Silicate‐substituted calcium phosphate (Si‐CaP) and unmodified hydroxyapatite (HA) to test whether these materials are capable of promoting osteogenic differentiation of MSCs in the absence of soluble factors. Si‐CaP supported attachment and proliferation of MSCs and induced osteogenesis to a greater extent than HA, as evidenced through upregulation of the osteoblast‐related genes: Runx2 (1.2 fold), Col1a1 (2 fold), Pth1r (1.5 fold), and Bglap (1.7 fold) Dmp1 (1.1 fold), respectively. Osteogenic‐associated proteins, alkaline phosphatase (1.4 fold), RUNX2, COL1A1, and BGLAP, were also upregulated and there was an increased production of mineralized bone matrix (1.75 fold), as detected by the Von Kossa Assay. These data indicate that inorganic substrates are capable of directing the differentiation programme of stem cells in the absence of known chemical drivers and therefore may provide the basis for bone repair in the clinical setting. © 2012 Wiley Periodicals, Inc. J Biomed Mater Res Part A: 101A:13–22, 2013.